Energy and exergy analyses of a gasoline engine - SAYIN, CENK (WILEY, 2007)
This study presents comparative energy and exergy analyses of a four-cylinder, four-stroke spark-ignition engine using gasoline fuels of three different research octane numbers (RONs), namely 91, 93 and 95.3. Each fuel test was performed by varying the engine speed between 1200 and 2400 rpm while keeping the engine torque at 20 and 40 Nm. Then, using the steady-state data along with energy and exergy rate balance equations, various performance parameters of the engine were evaluated for each fuel case. It was found that the gasoline of 91-RON, the design octane rating of the test engine, yielded better energetic and exergetic performance, while the exergetic performance parameters were slightly lower than the corresponding energetic ones. Furthermore, this study revealed that the combustion was the most important contributor to the system inefficiency, and almost all performance parameters increased with increasing engine speed. Copyright (c) 2006 John Wiley & Sons. Ltd.
Keywords: gasoline engine; octane number; energy analysis; exergy analysis; PERFORMANCE